Structural and biochemical insights into 7β‐hydroxysteroid dehydrogenase stereoselectivity. Issue 6 (6th April 2016) - Savino, Simone; Ferrandi, Erica Elisa; Forneris, Federico; Rovida, Stefano; Riva, Sergio; Monti, Daniela; Mattevi, Andrea
ABSTRACT: Hydroxysteroid dehydrogenases are of great interest as biocatalysts for transformations involving steroid substrates. They feature a high degree of stereo‐ and regio‐selectivity, acting on a defined atom with a specific configuration of the steroid nucleus. The crystal structure of 7β‐hydroxysteroid dehydrogenase from Collinsella aerofaciens reveals a loop gating active‐site accessibility, the bases of the specificity for NADP +, and the general architecture of the steroid binding site. Comparison with 7α‐hydroxysteroid dehydrogenase provides a rationale for the opposite stereoselectivity. The presence of a C‐terminal extension reshapes the substrate site of the β‐selective enzyme, possibly leading to an inverted orientation of the bound substrate. Proteins 2016; 84:859–865. © 2016 Wiley Periodicals, Inc.